Odpowiedzi

2010-03-23T14:25:50+01:00
A)
3x-3y+3=0
x+1/2y-2=0

x=2-1/2y

3(2-1/2y)-3y+3=0
6-1i1/2y-3y+3=0
-4i1/2y=-9
y=2

x=2-1
x=1
b)
2x+y=8
3x+y=11

y=8-2x

3x+8-2x=11
x=11-8
x=3

y=8-6
y=2

c)
2x+y=8
x=3

2*3+y=8
6+y=8
y=8-6
y=2

d)
-x-3y=5
y=-2x

-x-3(-2x)=5
-x+6x=5
5x=5
x=1

y=-2

e)
x+y=47
x-2y=11

x=47-y

47-y-2y=11
47-3y=11
-3y=11-47
-3y=-36
y=12

x=47-12
x=35
1 5 1
Najlepsza Odpowiedź!
2010-03-23T14:36:20+01:00
A)3x-3y=-3 3(-½y+2)=-3 -3/2 y+6=-3 -3/2y=-3-6 y=-9÷(-3/2) y=6
x=-½y+2
x=-½×6+2=-3+2=-1 x=-1 y=6

b) 2x+y=8 y=8-2x
3x+y=11 3x+8-2x=11 x=11-8=3 y=8-3x y=8-3×3=-1

x=3 y=-1

c)2x+y=8
x=3

2×3+y=8
y=8-6=2

x=3 y=2

d) -x-3y=5
y=-2x

-x-3(-2x)=5
y=-2x

-x+6x=5
y=-2x

5x=5 czyli x=1
y=-2x y=-2

e) x+y=47
x-2y=11

x=47-y
47-y-2y=11

x=47-y
-3y=11-47

x=47-y
-3y=-36

x=47-y
y=12

x=47-12=35
y=12


1 5 1